Relational-gestalt theory: The psychology of interpersonal conflict resolution - Talbot, Mike (Mediation Theory and Practice, 2017)
Current mediation practice lacks a coherent theory of the psychological factors that underlie interpersonal conflict and its resolution. Various models describe different ways to conduct mediation, yet there is insufficient explanation of the psychology of why and how these models often do, and sometimes do not, work. In this article, a new explanation of interpersonal conflict resolution is presented. Termed relational-gestalt theory, this explanation looks at conflict as a failure of an interpersonal relationship, and is based around the principles of gestalt theory. Relational-gestalt theory is compared with a number of extant mediation models, and its applicability is considered for various types and levels of disputes. The intention is to provide additional theoretical insights into the models and processes that guide the practice of interpersonal mediators, consultants and trainers.